TINDAK PIDANA REKAYASA GENETIKA DALAM HAL PANGAN MENURUT PERSPEKTIF HUKUM PIDANA - Aulia safa'atul uzmah; Idi Amin; Syamsul Hidayat (Fakultas Hukum Universitas Mataram, 2025)
This study seeks to examine the legal analysis of genetic technology innovations from the standpoint of criminal law. It adopts both normative and empirical legal research methods, employing a statute approach, a conceptual approach, and an analytical approach. Law No. 18 of 2012 concerning Food includes provisions under Article 133, which stipulates that food business operators who intentionally hoard or store food beyond the maximum quantity specified in Article 53—resulting in inflated prices of staple foods for profit—are subject to a maximum imprisonment of seven years or a fine of up to IDR 100 billion. The Indonesian government has established principles and regulatory standards governing the research and application of genetic engineering, including several laws related to biosafety and food security. Nevertheless, genetic engineering poses significant risks to the authenticity of genetic resources and ecological balance. This research recommends that the government intensify oversight by implementing laboratory testing procedures and establishing a regulatory body to monitor genetically modified seeds in Indonesia. Science and technology have long contributed to the improvement of human well-being and have continuously shaped modern lifestyles. The widespread use of chemical-based products and the growing application of genetic engineering in various sectors are part of broader efforts to enhance the quality of life. Through human intellect and innovation, genetically engineered products have been created with the aim of producing high-value goods that offer substantial added benefits to society—particularly in the agricultural sector